Penerapan Teknologi Produksi Biodiesel dari Minyak Jelantah pada Kelompok Masyarakat di Kampung Mokwam Distrik Masni Kabupaten Manokwari: - - Santoso, Budi; Murtiningrum; Aman, Wilson Palelingan (LPPM UPN Veteran Jakarta, 2023)
The acquisition of subsidized diesel fuel is challenging, and the elevated prices of non-subsidized diesel fuel have significantly impacted small and medium enterprise groups, causing operational issues. To mitigate this problem, it is vital to explore alternative fuels that can replace diesel fuel. Used cooking oil presents itself as a viable substitute for diesel fuel due to the abundance of cooking oil in households, which has the potential to cause environmental pollution. The esterification reaction can be employed to convert used cooking oil into biodiesel, suitable for use in diesel engines. This training aims to provide comprehensive guidance and practical training to Kharisma household business members on the production of biodiesel from used cooking oil. The training methods encompass lectures, discussions, and demonstrations. The reactor utilized has a 30-liter capacity for used cooking oil. The training results indicate that the Kharisma household business members are proficient in operating the biodiesel-making equipment (reactors) and are capable of independently producing biodiesel.